2015
DOI: 10.1185/03007995.2015.1058770
|View full text |Cite
|
Sign up to set email alerts
|

Association of obesity with glucose, blood pressure, and lipid goals attainment in patients with concomitant diabetes and hypertension

Abstract: A considerable proportion of dyslipidemia patients failed to achieve guideline-recommended targets in China, and this apparent treatment gap was more pronounced among women with central adiposity and patients with an elevated BMI. Based on the limitations of this cross-sectional study, further investigation of the mechanism at the molecular level is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…In the present study, the overall 3B goal attainment rates were significantly lower in MetS (2.1%) compared with non-MetS (10.2%) type 2 diabetes patients, even with higher medical coverage rates in MetS patients. As 50.8% of the MetS patients in the present study were diagnosed with abdominal obesity, these data are partly in agreement with recent publications, in which obesity was a factor for poor 3B control in Chinese type 2 diabetes patients 32,33 . Furthermore, our additional findings illustrate that blood lipid attainment might influence blood glucose attainment; patients who achieved their lipid control targets were more likely to achieve their target glucose level.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the overall 3B goal attainment rates were significantly lower in MetS (2.1%) compared with non-MetS (10.2%) type 2 diabetes patients, even with higher medical coverage rates in MetS patients. As 50.8% of the MetS patients in the present study were diagnosed with abdominal obesity, these data are partly in agreement with recent publications, in which obesity was a factor for poor 3B control in Chinese type 2 diabetes patients 32,33 . Furthermore, our additional findings illustrate that blood lipid attainment might influence blood glucose attainment; patients who achieved their lipid control targets were more likely to achieve their target glucose level.…”
Section: Discussionsupporting
confidence: 93%
“…This association was observed both across the trial population and after adjustment for potential confounding factors that are also related to obesity. These results are generally consistent with data from observational studies both in the general population and in high CV risk patients with T2DM [ 3 , 20 , 21 , 25 28 ]. Also, a significant association of reduced eGFR with BMI (but not WC) was observed, consistent with kidney dysfunction data from the BARI-2D trial [ 19 ].…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, post hoc analyses of the SCOUT trial that recruited patients ≥55 years confirmed a relationship between weight loss and CV risk factors (such as total cholesterol) and outcomes (such as CV mortality) [ 40 , 41 ]. Furthermore, although including patients <50 years, studies have shown an association of obesity with suboptimal control of CV risk factors in diabetic patients across the mean age range of 62–65.7 years [ 2 , 19 , 21 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…These are the expected lipid profiles in patients with obesity resulting from insulin resistance [34]. Overall, these metabolic disadvantages of Turkish patients with type 2 diabetes and obesity are similar to those populations from the different geographical regions of the world [10, 23, 35, 36]. Randomized controlled studies show that a significant proportion of patients with type 2 diabetes cannot reach prespecified targets for the major modifiable cardiovascular risk factors [37].…”
Section: Discussionmentioning
confidence: 99%